2011
DOI: 10.1016/j.ultsonch.2011.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Sonication improves kasturi lime (Citrus microcarpa) juice quality

Abstract: Freshly squeezed kasturi lime fruit juice was sonicated (for 0, 30 and 60min at 20°C, 25kHz frequency) to evaluate its impact on selected physico-chemical and antioxidant properties, such as pH, °Brix, titratable acidity, Hunter color values (L(∗), a(∗), b(∗)), ascorbic acid, DPPH radical scavenging activity, total phenolics, antioxidant capacity, flavonoids and flavonols. Additionally, the effect of sonication treatments on the microbial load (TPC, yeast and mold) were also evaluated. Sonication of juice samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

71
216
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(292 citation statements)
references
References 26 publications
71
216
1
4
Order By: Relevance
“…In a similar study, Bhat et al (2011) also found that ultrasound treatment did not give significant influence (p>0.05) on pH of kasturi lime juice in all the treatments. Meanwhile, the slight increase was observed in electrical conductivity of sonicated carrot juice compared to control as shown in Table 1.…”
Section: Effect Of Ultrasound Treatment On Ph and Electrical Conductimentioning
confidence: 57%
See 1 more Smart Citation
“…In a similar study, Bhat et al (2011) also found that ultrasound treatment did not give significant influence (p>0.05) on pH of kasturi lime juice in all the treatments. Meanwhile, the slight increase was observed in electrical conductivity of sonicated carrot juice compared to control as shown in Table 1.…”
Section: Effect Of Ultrasound Treatment On Ph and Electrical Conductimentioning
confidence: 57%
“…In recent studies about effect of sonication on apple juice (Abid et al, 2013), kasturi lime juice (Bhat et al, 2011), cantaloupe melon juice (Fonteles et al, 2012) and orange juice (Tiwari et al, 2008), ultrasound treatment technology has been proved to a desirable method of juice processing, which can avoid losses in beneficial nutrients and reduce the microbial load in the fruit juices. It is considered to be more advantageous due to its shortened processing time with lower energy consumption (Abid et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The ultra-sonication effects on color parameters of other fruit juices were previously reported by several researchers. For instance, Abid et al (2013) and Bhat et al (2011) respectively illustrated that the L and a* parameters of ultra-sonicated apple and kasturi lime juices were lower than the fresh juices, whereas the b* parameters increased noticeably. The significant decreases of those parameters in both grapefruit and Chokanan mango juices (Aadil et al 2013;Santhirasegaram et al 2013) were also observed.…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years, impact of sonication on raw juices from fruits and vegetables such as kasturi lime, cantaloupe melon, apple, orange, and carrot (Abid et al, 2013;Bhat et al, 2011;Fonteles et al, 2012;Jabbar et al, 2014;Tiwari et al, 2008) has been investigated and proved to an appropriate processing method of the juice. Sonication can effectively retain the most beneficial nutrients and decrease microbial load in the juice (Zou & Jiang, 2016).…”
Section: Introductionmentioning
confidence: 99%